Evaluating Effective Social Media Marketing With Artificial Intelligence Using The AIDA Model Approach - Alia, Putri Ariatna; Cahyono, Warna Agung; Shodikin, Mohamad; Meisyarani, Jihan Salsabila; Sani, Rosi Rijal; Kriswibowo, Rony (International Journal of Computer and Information System (IJCIS), 2024)
The rapid growth of information and communication technology, especially social media, has significantly changed the marketing landscape. In the face of this challenge, companies are increasingly adopting marketing strategies through social media to reach their intended target markets. This research aims to analyze the effectiveness of Social Media Marketing by utilizing Artificial Intelligence, especially ChattGPT and applying the AIDA Model approach (Awareness, Interest, Desire, Action). This research methodology uses descriptive qualitative methods with data collection through virtual ethnography and interviews from the Babelubozz online store using the Instagram platform: @grosirhijabtermurahsidoarjo. Artificial intelligence algorithms to analyze interaction patterns and user responses. The AIDA (Awareness, Interest, Desire, Action) model. used as a basis for measuring the stages of consumer awareness, interest, desire, and action in the context of marketing through social media. The results of this analysis provide an in-depth understanding of how companies can improve the effectiveness of their marketing campaigns on social media by optimizing each stage of the AIDA Model. Therefore, the marketing and promotional content generated by ChatGPT is able to increase the effectiveness of social media marketing.